A Family Medicine Perspective on Knee Osteoarthritis, Diabetic Neuropathy, and Metabolic Syndrome in A 73-Year-Old Male - Dwi Rahayu, Indriati; Norma Aini, Ilmania (Jurnal Ilmu Kedokteran Keluarga, 2026)
This case report explores the complex interplay of knee osteoarthritis (OA), diabetic neuropathy, andmetabolic syndrome in a 73-year-old male, highlighting the challenges in diagnosis and management from a family medicine perspective. The coexistence of these conditions requires a holistic, patient-centered approach focusing on pain management, lifestyle modification, and family involvement to improve adherence and outcomes. This study highlights the importance of early detection andcomprehensive care to prevent severe complications, improve quality of life, and address the limitationsposed by OA on physical activity necessary for metabolic control.